DESIMINASI PENGEMBANGAN INOVASI TEKNOLOGI MESIN PENGERING PADA UMKM KERIPIK NANAS MADU DI KABUPATEN LAMPUNG TIMUR - Muhammad Husaini; Diki Danar Tri Winanti; Maulid Wahid Yusup (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2024)
: The research results dissemination program is one of the technology transfer activities to the community, which is in line with one of the visions of the University of Lampung, namely planning, implementing, controlling and evaluating research and community service to improve the quality of education and community welfare. Drying pineapple fruit is a technique for processing fruit into fruit chips using a frying process that is carried out using low pressure, almost the same as a vacuum. The output targets of this research results dissemination program are (1) improving skills in processing agricultural fruit, (2) increasing the productivity of agricultural products (3) building effective partnerships and collaboration between universities and community groups, (4) developing collaborative empowerment pattern through assistance in the transfer of skills, capital and wider marketing access. The methods used in empowerment are based on business feasibility, product availability, product economic value, availability of managing human resources, technology, financial aspects and social impacts.